Survey of company reports : an analysis of current practices in presenting information - Platt, C. J. (Farnborough, England : Wilton Publications, 1978)
The object of this book is to depict some of the more interesting features of accounting and reporting practices adopted by listed companies in their published reports.
osc 30/01/2019
Loans
Keywords: Financial statements; Corporations; Corporation reports